Drinking wine to "get high": The influence of awareness of the negative effects among young adults. (December 2018) - Ferretti, Fabio; Pozza, Andrea; Harri, Pepita; Francalanci, Claudia; Gualtieri, Giacomo; Coluccia, Anna
Abstract: Introduction: In a group of university students, the current study investigated the relationship between drinking wine to get high and the awareness about its characteristics, composition, positive and negative effects on health. Methods: Through a web-based survey, 1685 students at the University of Siena completed a self-report questionnaire to assess consumption behaviours, knowledge about wine and the awareness about its effects. Results: Seventy-three percent reported drinking wine. Males were more frequently wine consumers ( p  = 0.037). Among the students who reported drinking, 69.3% engaged this habit during the weekend. Almost 12% reported drinking wine to get high. Drinking wine to get high correlated with the consideration of its consumption: using this beverage to get high was strongly associated with considering wine like other spirits ( p  = 0.033). Conclusions: Older age, female gender, and considering wine as a part of the diet were found to be protective factors against wine drinking-to get high. In contrast with some literature, awareness of the negative effects correlated with higher propensity to use wine to get high. Potential interpretations and limitations are addressed. Highlights: Wine is frequently used by young people to get high, similarly to other spirits. Gender and age affect wine drinking behaviours. Gender and age do not mediate the awareness on wine drinking-to get high. Being female and older are protective factors against abuse of wine. The knowledge about negative effects influence the likelihood of using wine to get high.